A perovskite material thick film integration method assisted by anisotropic conductive adhesive bonding

CN117545331BActive Publication Date: 2026-10-30UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311602134.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-10-30
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

然而,采用溶液法、刮涂法制备出的大面积厚膜在其降温结晶生长过程中,由于钙钛矿厚膜材料与衬底的热膨胀系数E不同,使得二者收缩程度不一致,产生的热应力致使光吸收层表面出现划痕、开裂,甚至使其直接与底层衬底分离,最终导致整个器件的失效,这严重制约了X射线探测领域的发展

Benefits of technology

[0004]针对上述存在的问题或不足,本发明提供了一种异方性导电胶膜(ACF,Anisotropic Conductive Film)辅助键合钙钛矿材料厚膜集成方法,改善衬底与钙钛矿层热膨胀系数不匹配问题,防止脱落现象发生,实现钙钛矿和衬底之间坚固的机械连接和电信号传输,解决钙钛矿基X射线探测材料与基底键合问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117545331B_ABST
    Figure CN117545331B_ABST
Patent Text Reader

Abstract

The application discloses a kind of anisotropic conductive adhesive assisted bonding perovskite material thick film integration method, it is related to radiation detection field, specifically related to a kind of bonding method of perovskite material thick film and conductive substrate.The application is by attaching anisotropic conductive adhesive film on the surface of clean conductive substrate, by heating and pressurizing means, the upper layer light absorption layer thick film material is bonded together with lower layer conductive substrate, forms vertical structure X-ray detector, solves the technical problem that lead-based halogen perovskite direct X-ray detection material thick film and lower layer conductive substrate fall off in prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radiation detection, and more specifically to a method for thick-film integration of perovskite materials assisted by anisotropic conductive adhesive. Background Technology

[0002] High-absorption-coefficient, high-performance X-ray detection materials are the core technology of medical digital imaging systems. There are two main methods for converting X-rays into electrical signals: indirect imaging and direct imaging. Indirect imaging uses scintillator materials to indirectly convert high-energy X-ray photons into ultraviolet or visible light, and then uses photodiodes to detect these signals. This multi-step signal conversion results in high energy loss, requires a high imaging dose, and leads to low spatial resolution due to optical crosstalk between scintillators. Direct imaging uses semiconductor materials to directly convert X-ray photons into electrical signals. Photogenerated carriers are directionally transported under the influence of an electric field and collected by electrodes. Imaging requires only one signal conversion step, requires a lower imaging dose, and significantly reduces pixel crosstalk, thus achieving higher spatial resolution and simpler system configuration. Commonly used semiconductor materials for this technology, such as amorphous selenium (α-Se), exhibit low sensitivity and a high detection limit due to its low carrier mobility-lifetime product, low atomic number, and the need for a high operating electric field.

[0003] Lead-based halide perovskite materials, such as methylamine lead iodide (MAPbI3) and cesium lead bromine (CsPbBr3), possess advantages such as high X-ray absorption coefficients, high carrier mobility-lifetime products, low trap density, and low cost, making them a research hotspot in X-ray detection absorbing layers in recent years. High-quality absorbing layers are one of the foundations for fabricating X-ray detection devices, and how to fabricate high-quality absorbing layers plays a crucial role in improving detector performance. Furthermore, high-performance X-ray detectors require perovskite absorbing layer materials with a thickness of several hundred micrometers to ensure sufficient absorption of high-energy rays. For large-area X-ray imaging devices, perovskite light-absorbing layer materials can be fabricated using methods compatible with transistor (TFT) technology, such as solution methods and blade coating methods, which can relatively easily achieve X-ray area array detection and imaging. However, during the cooling and crystallization growth process of large-area thick films prepared by solution methods and blade coating methods, the different thermal expansion coefficients E of the perovskite thick film material and the substrate cause inconsistent shrinkage between the two. The resulting thermal stress causes scratches and cracks on the surface of the light absorption layer, and may even cause it to separate directly from the underlying substrate, ultimately leading to the failure of the entire device. This seriously restricts the development of the X-ray detection field. Summary of the Invention

[0004] To address the aforementioned problems or shortcomings, this invention provides a thick-film integration method for perovskite materials assisted by anisotropic conductive film (ACF), which improves the mismatch in thermal expansion coefficients between the substrate and the perovskite layer, prevents detachment, achieves a robust mechanical connection and electrical signal transmission between the perovskite and the substrate, and solves the bonding problem between perovskite-based X-ray detection materials and the substrate.

[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for thick-film integration of perovskite materials using anisotropic conductive adhesive-assisted bonding is disclosed, which is used to press-bond material layers to a substrate to fabricate an X-ray direct photoelectric conversion detector. The specific steps are as follows:

[0007] S1: Preparation of perovskite precursor solution: The perovskite (ABX3) precursor solution is prepared by mixing AX and BX2 in a certain molar ratio, dissolving in an organic solvent, and stirring on a magnetic stirrer at 60℃ for 8-12 hours until the solute is completely dissolved, thus preparing a 0.01-100mol / L perovskite precursor solution.

[0008] In this context, the element at position A is Cs, MA, or FA, the element at position B is Pb, and the element at position X is I or Br.

[0009] The organic solvent is any one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) or 1,4-butyrolactone;

[0010] S2: Perform surface cleaning treatment on the pre-deposited substrate;

[0011] S3: Attach the ACF adhesive to the substrate surface. First, peel off the top film of the ACF adhesive and adhere it to the electrode of the substrate after precise alignment. Before depositing the material, peel off the other bottom film of the ACF adhesive. Then, use ultrasonic spraying or blade coating to prepare a thick film on the substrate with the ACF adhesive.

[0012] Ultrasonic spraying process: Before spraying, a certain amount of N,N-dimethylformamide (DMF) solvent is added to the ABX3 / organic solvent precursor solution to dilute the molar concentration of the precursor solution to 2-8 times the original concentration, forming the ABX3 / organic solvent / DMF precursor solution; during ultrasonic spraying, the precursor solution forms aerosol droplets under the ultrasonic atomizer, and then the carrier gas carries the droplets to the nozzle and sprays them out;

[0013] The ultrasonic atomizer has a power of 1-10W, and the carrier gas is oxygen or nitrogen; the spraying speed is 5-60mm / s, and the interval between two spraying processes is 40-80s; the substrate temperature is maintained at 50-200℃ during the spraying process, and the air flow rate is 0.1-1L / min to maintain the balance between material crystallization and volatilization rates; the film thickness is increased by repeating the spraying process, with a cycle count of 80-160 times.

[0014] Blade coating process: First, determine the required height of the blade to be adjusted to 100-500μm. After adjusting the height, use a pipette to draw 0.5-5ml of precursor solution and drop it onto the substrate, being careful not to generate air bubbles in the liquid. Set the blade moving speed to 5-50mm / s and start the coating machine to perform the blade coating. After coating, quickly transfer the material into an oven and anneal at 150℃ for 1 hour to completely remove the solvent.

[0015] S4: Cooling; The substrate is slowly cooled from the sample preparation temperature to 40-80℃, and the stress is gradually released at a cooling rate of 0.1-10℃ / min;

[0016] S5: Use a hot press to hot press the perovskite light absorption layer material; after heating and pressurizing for 10s-60s, the ACF adhesive breaks the insulating layer to expose the conductive particles and cures, achieving the effect of circuit connection. The heating temperature is 150-300℃ and the pressure is set to 0.1MPa-20MPa.

[0017] Furthermore, a hydrophobic PI film can be coated on the thick perovskite film before hot pressing to prevent the thick film from being peeled off by the mold.

[0018] S6: Electrode paste is coated on the surface of the light-absorbing layer to form a vertical X-ray detector.

[0019] Furthermore, arrayable and patternable ACF adhesives can be used to integrate conductive adhesives with substrates, enabling customized design of detector device structures.

[0020] Anisotropic conductive film (ACF) is a polymer material with a metal coating on its surface. Its core material is a polymer or glass microspheres, and the coating material can be gold, silver, copper, nickel, etc. When ACF is attached between a lower substrate and an upper perovskite material, the ACF matrix softens and does not solidify at room temperature, remaining in a liquid colloidal state. After heating and pressurizing in a hot press, the curing agent and insulating resin react completely, forming a mechanical connection between the substrate and the upper electronic material. Simultaneously, the randomly distributed conductive microspheres within the ACF deform, resulting in a large contact area between the surface metal conductive layer and the substrate, forming a conductive path in the Z-direction. Meanwhile, the filler content, below the percolation threshold, limits its conductivity in the XY directions, thus exhibiting anisotropic electrical properties.

[0021] The high-quality perovskite thick film prepared by this method forms a device structure with vertical conduction and lateral insulation under hot pressing and high temperature conditions. It has both excellent mechanical properties and X-ray photoelectric response characteristics, and can realize the function of direct X-ray detection. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the thick film preparation process of perovskite material assisted bonding by anisotropic conductive adhesive film according to the present invention.

[0023] Figure 2 This is a SEM cross-sectional image of the perovskite thick film prepared according to the present invention;

[0024] Figure 3 XRD data of the perovskite thick film prepared in this invention;

[0025] Figure 4 Photoelectric data of the perovskite thick film prepared in this invention under a 5V bias voltage;

[0026] Figure 5 Photoelectric data of the perovskite thick film prepared in this invention under bias voltages of 5V, 20V and 50V. Detailed Implementation

[0027] To make the above-described process of the present invention easily understandable, the present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. The following embodiments are only used to further illustrate the present invention and do not limit the content of the invention itself. Those skilled in the art can make some non-essential improvements and adjustments based on the present invention.

[0028] Example 1

[0029] S1: As Figure 1 As shown in (a), 1.299 g CsI and 2.305 g PbI2 (molar ratio 1:1) were dissolved in 5 ml of DMSO solvent and stirred at 60 °C for 8 hours on a magnetic stirrer to prepare a 1 mol / L perovskite precursor solution.

[0030] S2: Size is 15×15mm 2 The conductive indium tin oxide (ITO) substrate was ultrasonically cleaned in distilled water and ethanol for 15 minutes each, and then dried with nitrogen gas.

[0031] S3: As Figure 1 As shown in (b), ACF adhesive was attached to the substrate surface at room temperature; before spraying, 35 mL of DMF solvent was added to the clarified perovskite precursor solution for dilution; as follows Figure 1As shown in (c), the precursor solution was atomized using 3W ultrasonic vibration, and the nozzle continuously and repeatedly supplied the mist to the preheated substrate. During the spraying process, the substrate heating stage temperature was set to 100℃, the nozzle moving speed was 5mm / s, and the solution flow rate was 1ml / min; the number of solution deposition cycles was set to 80, and the interval between two spraying cycles was 10s.

[0032] S4: After spraying, the substrate will naturally cool from 100°C to 40°C.

[0033] S5: As Figure 1 As shown in (d), the perovskite substrate was transferred to a hot press for hot pressing and curing. A hydrophobic PI film was then coated onto the thick perovskite film to prevent it from peeling off during pressing. The hot pressing conditions were: hot pressing time of 30 s, bonding temperature of 250℃, and bonding pressure of 2 MPa. After heating and pressurizing the substrate for 30 s, the ACF adhesive broke down the insulating layer, exposing the conductive particles, which then cured. The conductive particles connected the material layer to the substrate, enabling conductivity and achieving a vertically connected circuit.

[0034] SEM cross-section as shown Figure 2 As shown, the anisotropic conductive adhesive improved the film quality of the perovskite material layer. The perovskite film was dense, with a thickness of approximately 151 μm. The film surface was smooth, with no obvious pinholes, cracks, or detachment from the substrate, exhibiting excellent mechanical properties. The perovskite thick film prepared by anisotropic conductive adhesive-assisted bonding not only has tight contact with the substrate, but its dense and smooth morphology also helps to improve the photoelectric properties of the perovskite thick film. XRD patterns are shown below. Figure 3 As shown, the thick film is composed of orthorhombic δ-CsPbI3 material with high structural stability.

[0035] S6: For X-ray response testing, such as Figure 1 As shown in (e), a contact electrode is prepared by coating a conductive silver paste onto the material surface. The electrode shape is determined using a metal mask, with an area of ​​0.09 cm². 2 A square block was formed and dried in an oven at 60℃ for 1 hour to prepare a vertically conductive ITO / ACF / CsPbI3 / Ag X-ray detector. Its structural schematic diagram is shown below. Figure 1 As shown in (f), for X-ray response testing, an 80kV tube voltage was used to measure the photocurrent and dark current at different locations (points 1 and 2) and under an applied 5V bias voltage, thereby calculating the device's sensitivity to X-ray response. Figure 4 Fitting the relationship between photocurrent density and X-ray dose rate yields sensitivities of 493.95 μC·Gy at points 1 and 2 under a 5V bias. -1 ·cm -2 and 887.01 μC·Gy -1 ·cm-2 . Figure 5 The sensitivity of the detector under applied bias voltages of 5V, 20V, and 50V is presented. When the applied bias voltage reaches 50V, the photocurrent is close to saturation, and increasing the dose does not significantly increase the number of photogenerated carriers. In summary, the X-ray detector exhibits excellent X-ray photoelectric response characteristics.

[0036] Example 2

[0037] S1: Dissolve 2.384 g MAI and 6.915 g PbI2 (molar ratio 1:1) in 5 ml of γ-butyrolactone solvent, place on a magnetic stirrer and heat at 60 °C for 12 hours to prepare a 3 mol / L perovskite precursor solution.

[0038] S2: Take a 64*64 resolution transistor array (TFT) sensor chip and ultrasonically clean it for 15 minutes each in ethanol and distilled water, then dry it with nitrogen gas.

[0039] S3: Apply ACF adhesive parallel to the TFT surface. Set the height between the squeegee and the substrate to 200µm, and fix the squeegee movement speed at 25mm / s. After adjusting the height, use a pipette to draw 3ml of perovskite precursor solution and drop it onto the substrate, being careful not to generate air bubbles in the liquid. Start the coating machine to perform the coating. After coating, quickly transfer it to an oven for annealing at 150℃ for 1 hour to completely remove the solvent.

[0040] S4: During the sample cooling stage, the substrate is slowly reduced from the sample preparation temperature to 60°C, and the stress is gradually released at a cooling rate of 1°C / min.

[0041] S5: Transfer the perovskite-grown substrate to a hot press stage, and cover it with a hydrophobic PI film to prevent the thick film from being peeled off by the mold. Set the bonding temperature to 250℃ and the bonding pressure to 2MPa. After heating and pressurizing the substrate for 45 seconds, the ACF adhesive breaks down the insulating layer, exposing the conductive particles, and then cures, achieving the effect of circuit connection.

[0042] S6: Using a metal mask to apply conductive silver paste, contact electrodes for the pixel area and Vss common electrode area are fabricated on the surface of the perovskite material. The perovskite X-ray imaging plate is then dried in a 60°C oven for 1 hour to obtain the perovskite X-ray imaging plate for X-ray detection and imaging.

Claims

1. A method for thick-film integration of perovskite materials assisted by anisotropic conductive adhesive, characterized in that, Includes the following steps: S1: Preparation of perovskite precursor solution: The perovskite ABX3 precursor solution is prepared by mixing AX and BX2 in a certain molar ratio, dissolving in an organic solvent, and stirring on a magnetic stirrer at 60℃ for 8-12 hours until the solute is completely dissolved, thus preparing a 0.01-100mol / L perovskite precursor solution. In this context, the element at position A is Cs, MA, or FA, the element at position B is Pb, and the element at position X is I or Br. S2: Perform surface cleaning treatment on the pre-deposited substrate; S3: ACF adhesive is attached to the substrate surface, and then a thick film is prepared on the substrate with ACF adhesive by ultrasonic spraying or blade coating. The ultrasonic spraying process is as follows: Before spraying, a certain amount of N,N-dimethylformamide solvent is added to the ABX3 / organic solvent precursor solution to dilute the molar concentration of the precursor solution to 2-8 times the original concentration, forming an ABX3 / organic solvent / N,N-dimethylformamide precursor solution; during ultrasonic spraying, the precursor solution forms aerosol droplets under the ultrasonic atomizer, and then the carrier gas carries the droplets to the nozzle and sprays them out. The blade coating process is as follows: First, determine the height that the blade needs to be adjusted to be 100-500μm. After adjusting the height, use a pipette to draw 0.5-5ml of precursor solution and drop it onto the substrate, being careful not to generate air bubbles in the liquid. Set the blade moving speed to 5-50mm / s and start the coating machine to perform the blade coating. After coating, quickly transfer the material into an oven and anneal at 150°C for 1 hour to completely remove the solvent; S4: Cooling; The substrate is slowly cooled from the sample preparation temperature to 40-80℃, and the stress is gradually released at a cooling rate of 0.1-10℃ / min; S5: Use a hot press to hot press the perovskite light absorption layer material; after heating and pressurizing for 10s-60s, the ACF adhesive breaks the insulating layer to expose the conductive particles and cures, achieving the effect of circuit connection. The heating temperature is 150-300℃ and the pressure is set to 0.1MPa-20MPa. S6: Electrode paste is coated on the surface of the light-absorbing layer to form a vertical X-ray detector.

2. The method for thick-film integration of anisotropic conductive adhesive-assisted bonding of perovskite materials according to claim 1, characterized in that, The organic solvent is any one of dimethyl sulfoxide, N,N-dimethylformamide, or 1,4-butyrolactone.

3. The method for thick-film integration of anisotropic conductive adhesive-assisted bonding of perovskite materials according to claim 2, characterized in that, The ultrasonic atomizer has a power of 1-10W, and the carrier gas is oxygen or nitrogen; the spraying speed is 5-60mm / s. During the spraying process, the substrate temperature is maintained at 50-200℃ and the air flow rate is 0.1-1L / min to maintain the balance between the material crystallization and volatilization rates. The film thickness is increased by repeating the spraying process, with 80-160 cycles and an interval of 40-80 seconds between two spraying processes.

4. The method for thick-film integration of anisotropic conductive adhesive-assisted bonding of perovskite materials according to claim 3, characterized in that, In step S5, a hydrophobic PI film is coated on the thick perovskite film before hot pressing to prevent the thick film from being peeled off by the mold.

5. The method for thick-film integration of anisotropic conductive adhesive-assisted bonding of perovskite materials according to claim 4, characterized in that, Arrayable and patternable ACF adhesives can be integrated with substrates to customize the device structure of detectors.

6. The method for thick-film integration of anisotropic conductive adhesive-assisted bonding of perovskite materials according to claim 5, characterized in that, The substrate is either conductive indium tin oxide or a transistor array sensor chip.

Citation Information

Patent Citations

  • Manufacturing method of X-ray detector

    CN116249361A

  • High-quality perovskite thick film and preparation method and application thereof

    CN116940190A